CycloBranch 2: Molecular Formula Annotations Applied to imzML Data Sets in Bimodal Fusion and LC-MS Data Files - Novák, Jiří; Škríba, Anton; Havlíček, Vladimír (Analytical chemistry, 2020)
Natural product chemistry, microbiology, and food, human, and plant metabolomics represent a few sources of complex metabolomics data generated by mass spectrometry. Among the medley of software tools used to handle these data sets, no universal tool can qualitatively, quantitatively, or statistically address major biological questions or tasks. CycloBranch 2, an open and platform-free software, at least now provides the de novo generation of molecular formulas of unknown compounds in both liquid chromatography/mass spectrometry and mass spectrometry imaging datafiles. For imaging files, this database-free approach was documented in the bimodal image fusion and characterization of three small molecules, including metallophores. The fine isotope ratio data filtering step distinguished 34S/13C2 and 41K/13C2 features. The standalone software package is implemented in C++ and can be downloaded from https://ms.biomed.cas.cz/cyclobranch/ and used under GNU General Public License.
Keywords: Mass Spectrometry; hmotnostní spektrometrie; Software; biologické přípravky; Databases, Factual; software; molekulová hmotnost; Molecular Weight; Chromatography, Liquid; databáze faktografické; Biological Products; chromatografie kapalinová